Al-Durus al-Mustafadah min Surah Yusuf li Al-Syabab al-Muslim al-Muasir - Mohd Shafiee, Hamzah (2018)
The present era is witnessing the appearance of indecency among the Muslim youths due to influence of complicated orientations. These orientations are of different types; readable, visual and audio, and they have negatively affected the morals of many Muslim youths. They also lead the youths to imitation of the West or the East in terms of dress, feeling and movements, as they read, listen or watch what these civilizations have offered them. Therefore, this research aims to contribute to confronting these complicated orientations among contemporary Muslim youth through the story of Yusuf (peace be upon him). This story is a perfect model for preserving the contemporary Muslim youth from the negative influences of these orientations. In order to achieve these objectives, the study used descriptive and deductive methods, The study found that the story of Yusuf (peace be upon him) included several lessons that can be employed in the formation of contemporary Muslim personality, exemplification self-protection with fear of Allah, seeking help from Allah, good deeds, foresight, and other qualities that inspire people on steadfastness and facing adversity. The current Muslim need to follow the story of Yusuf (peace be upon him) to take a lesson from it, And to protect himself from the distracting causes which one can attract him from several sources.